2012
DOI: 10.1002/cpe.2812
|View full text |Cite
|
Sign up to set email alerts
|

Towards the optimal synchronization granularity for dynamic scheduling of pipelined computations on heterogeneous computing systems

Abstract: Loops are the richest source of parallelism in scientific applications. A large number of loop scheduling schemes have therefore been devised for loops with and without data dependencies (modeled as dependence distance vectors) on heterogeneous clusters. The loops with data dependencies require synchronization via cross-node communication. Synchronization requires fine-tuning to overcome the communication overhead and to yield the best possible overall performance. In this paper, a theoretical model is present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Comparison of 3D and 2D Tiling. As mentioned in the related work, the proposed methods in [21,33,40] could find the near-optimal partitioning of 3-nested loop with dependencies for homogeneous/heterogeneous computing systems. It targets two loops of the nested loop and considers the outer loop as synchronization dimension and another loop as scheduling dimension.…”
Section: 2mentioning
confidence: 96%
See 3 more Smart Citations
“…Comparison of 3D and 2D Tiling. As mentioned in the related work, the proposed methods in [21,33,40] could find the near-optimal partitioning of 3-nested loop with dependencies for homogeneous/heterogeneous computing systems. It targets two loops of the nested loop and considers the outer loop as synchronization dimension and another loop as scheduling dimension.…”
Section: 2mentioning
confidence: 96%
“…In distributed-memory parallel systems, communication and synchronization overhead between the nodes are the important reasons of the performance degradation when running dependence loops. So, we use coarse-grain pipeline parallelism to balance trade-offs between parallelization, communication and synchronization overhead [20,33].…”
Section: Background and Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…A two-phase scheme is proposed to solve parallel regular loop scheduling problem in heterogeneous grid computing environments in [16]. In [17][18][19] new results are presented for loops with dependencies. Recent research results [20,21] have been reported for designing loop self-scheduling methods for grids.…”
Section: Related Workmentioning
confidence: 99%